ANALYSIS OF AUTHENTICITY OF TEACHERS’ MADE ASSESSMENT AND ITS CONTRIBUTION TO STUDENTS’ ENGLISH ACHIEVEMENT (A STUDY IN JUNIOR HIGH SCHOOLS IN BULELENG REGENCY) - Ni Luh Putu, Era Adnyayanti; A.A.I.N, marhaeni; Luh Putu, Artini (Jurnal Pendidikan Bahasa Inggris Indonesia, 2013)
This research aimed at analyzing the authenticity of teacher?s made assessment and its contribution to students? English achievement. 35 Junior High School English teachers in Buleleng Regency were used as the subjects in this research. Data collection methods employed were document study, questionnaire, and interview to answer the research questions quantitatively and qualitatively. The findings demonstrated that teachers? made assessments have sufficient authenticity level of planning, have high authenticity level of assessment implementation as perceived by teachers, have sufficient authenticity level of assessment implementation as perceived by students, and  is considered as having high level on the students? English achievement after being assessed with teachers? made assessment. The findingsalso showed that only assessment implementation as perceived by studentsand simultaneous predictors gave significant contribution to students? English achievement. Assessment planning and assessment implementation as perceived by teachers did not show significant contribution because there was found inconsistent finding between what teachers planned with what teachers have implemented. This study has positive contribution to the importance of considering the authenticity of assessment in teaching English as a foreign language.Key Words: authenticity, authentic assessment, teachers? made assessment, students? achievement